ANALISA BREAK EVENT POINT (BEP) TERHADAP LABA PERUSAHAAN - Muhammad Yusuf (Faculty of Economic and Business, 2014)
Break event point or the break-even point can be defined as a situation where the operating company does not make a profit and not a loss. The goal is to provide the knowledge to increase knowledge about the break event point (the point of principal) and its relationship with the company profit and to know how the results of the. Analysis break event point is very important for the leadership of the company to determine the production rate how much the cost will be equal to the amount of sales or in other words to determine the break event point we will determine the relationship between sales, production, selling price, cost, loss or profit, making it easier for leaders to take discretion.DOI: 10.15408/ess.v4i1.1955